LRP1B Suppresses Immunotherapy Efficacy in Lung Adenocarcinoma by Preventing Ferroptosis - Zi‐Hao Ke; Ying Chen; Tao Yu; Qi Zhang; Yan Xiang; Kai‐Hua Lu (Cancer Medicine)
ABSTRACT Background Immune biomarkers for non‐small‐cell lung cancer (NSCLC) are programmed death ligand 1 (PD‐L1) and tumor mutational burden (TMB). However, they cannot accurately predict the effectiveness of immunotherapy. Identifying appropriate biomarkers that can differentiate between beneficiary groups is imperative. Methods We identified lipoprotein receptor–related protein 1B (LRP1B) mutation as a potential biomarker for immunotherapy by analyzing clinical data, combined with bioinformatics analysis. The effects of LRP1B on ferroptosis were assessed using qRT‐PCR, Western blotting, CCK‐8 assay, and flow cytometry. The potential mechanism underlying the regulation of ferroptosis by LRP1B was elucidated using qRT‐PCR, Western blotting, ChIP, and dual‐luciferase reporter gene assays. Results Through the collection and analysis of clinical data, we had established that LRP1B mutations are closely associated with immunotherapy. Bioinformatics analysis revealed significant differences in the expression levels of PD‐L1 and TMB between patients with LRP1B mutation and wild‐type patients in lung adenocarcinoma (LUAD). Furthermore, we observed that patients with LRP1B mutation in LUAD had significantly higher levels of tumor‐infiltrating lymphocytes (TILs) than wild‐type patients. In addition, we found that patients with LRP1B mutation in LUAD had significantly prolonged progression‐free survival (PFS) compared to wild‐type patients. However, the differences of PD‐L1 expression, TILs, and PFS were not observed in patients with LRP1B mutation in lung squamous cell carcinoma (LUSC). These findings provided strong evidence that LRP1B mutation was a potential biomarker for immunotherapy in LUAD. Moreover, our in vivo experiments indicated that knockdown of LRP1B enhanced the efficacy of mPD‐1, and mechanistic studies revealed that LRP1B regulated the sensitivity of cells to ferroptosis by modulating the expression of SLC7A11 through altering the phosphorylation level of STAT3. Further analysis revealed that LRP1B knockdown promoted immunotherapy in vivo. Conclusions Our results confirmed that LRP1B affected the efficacy of immunotherapy by modulating the sensitivity of NSCLC cells to ferroptosis. LRP1B mutations represent a highly promising immunotherapeutic biomarker for NSCLC.